Between the real and the symbolic: a psychological analysis of the bond with reborn babies - Mildenberg, Emerson (Revista Terra & Cultura: Cadernos de Ensino e Pesquisa; Vol 41 No 78 (2025): Publicação Contínua, 2025)
The phenomenon of using realistic dolls, known as reborn babies, has gained notoriety, especially among adult women who treat them as if they were living babies, feeding them, taking them to fictitious "doctor's" appointments, among other behaviors. In extreme cases, these people even claim that the doll "is hungry", "needs vaccinations" or "needs to sleep". Although at first glance it may seem like just a form of play or collecting, there are cases in which the behavior points to deeper psychological issues.